Sociology of Law Study: The Effect of Sidewalk Vendors on Pedestrians in Sidoarjo - TRI DEWI MAHARANI, NABILA; Syaifullah, Khalid (Veteran Law Review, 2025)
This study investigates the problems arising from the use of sidewalks by street vendors in Sidoarjo, East Java, Indonesia. The purpose of this study was to investigate the influence of the presence of street vendors on pedestrian facilities, their socio-economic conditions, as well as the point of view of the sociology of law on this issue. The method applied in this study is qualitative with the sociology of law approach. Data collection is done through literature research. Findings from the study suggest that the presence of street vendors has a major impact on pedestrian infrastructure, often resulting in disruption and discomfort for people walking. In the socio-economic aspect, street vendors play a vital role in providing employment and income opportunities for low-income citizens, they also face various problems such as relocation and lack of access to capital. The point of view of the sociology of law highlights that there is a tension between existing legal norms and social practices related to the use of public spaces. The study concludes that it is critical to develop more comprehensive and sustainable policies, which not only regulate street vendors but also support them economically and socially and involve them in the decision-making process.